Impact of single nucleotide polymorphism on short stature and reduced tongue pressure among community-dwelling elderly Japanese participants: a cross-sectional study - Yuji Shimizu; Shimpei Sato; Yuko Noguchi; Jun Koyamatsu; Hirotomo Yamanashi; Miho Higashi; Mako Nagayoshi; Koichiro Kadota; Shin-Ya Kawashiri; Yasuhiro Nagata; Noboru Takamura; Takahiro Maeda (Komiyama Printing Co. Ltd, 2017)
Abstract Background Asian-specific single nucleotide polymorphism (SNPs) (rs3782886) is reported to be associated with myocardial infarction; sarcopenia is reported to be associated with coronary subclinical atherosclerosis. On the other hand, short stature has been revealed as an independent risk factor for cardiovascular disease. However, no studies have reported on the association between sarcopenia and short stature nor on the impact of rs3782886 on this association. Methods Since reduced maximum voluntary tongue pressure against the palate (MTP) reflects one aspect of sarcopenia, we conducted a cross-sectional study of 537 community-dwelling elderly Japanese participants aged 60-89 years who had participated in a general health checkup in 2015. Short stature was defined as values at or under the 25th percentile, and reduced MTP was defined as the lowest tertile of the study population (<158.0 cm and <26.5 kPa for men, <145.0 cm and <24.1 kPa for women). Results Independent of classical cardiovascular risk factors, short stature was revealed to be positively associated with reduced MTP. The adjusted-odds ratio (OR) and 95% confidence interval (CI) of reduced MTP for short stature was 1.87 (1.19, 2.94). We also found that independent of known cardiovascular risk factors, with the non-minor homo of rs3782886 taken as the reference group, the adjusted OR and 95% CI for short stature and reduced MTP of the minor homo allele were 3.06 (1.23, 7.63) and 3.26 (1.33, 8.03), respectively. Conclusion Short stature is independently associated with reduced MTP, with Asian-specific SNPs possibly playing an important role in this association.